"To a Dog, a Dog's Death!": Naïve Monarchism and Regicide in Imperial Russia, 1878–1884. Issue 1 (2021) - Beer, Daniel
Abstract : The article examines arrest protocols drawn up from the mid-1870s to the mid-1880s by local policemen investigating thousands of individuals denounced to the authorities for having voiced criticisms of the monarchy and approval of the campaign of terror in the reign of Alexander II. The discussion proceeds in two stages. It first argues that the arrest protocols constitute grounds for a revisionist challenge to the existing historiography which charts enduring, if gradually declining, popular support for the monarchy in the final decades of tsarism. It then argues for a reappraisal of the efforts by revolutionaries in the reign of Alexander II to destroy the sanctity of the autocracy through the use of "propaganda by the deed." The campaign to assassinate the tsar emerges in the arrest protocols as an effective form of political messaging that gained real purchase in the popular imagination. It prompted lower-class Russians to articulate their own local grievances in terms of popular sovereignty, natural justice and political accountability.